Firsts in their field: the perceptions of women who have led the way - Margaret Stone; Margaret Stone; Pippa Chapman; Urvi Khasnis; David Collins (Frontiers in Sports and Active Living)
The role women play in sport has been the subject of considerable discussion and research since the nineteen seventies. Much of this research has been descriptive or focused on the barriers, women face in advancing into a leadership role in a sporting organization. In an attempt to enrich the picture, women role models who occupy or have occupied leadership roles in sporting organizations were identified to gain their perspective, in their own words, on the challenges and requirements needed to be successful. The experience of these high achieving women has value in paving the way for future generations with ambitions to succeed in a leadership role in sport. Six women were identified and interviewed as the first to occupy their position in a sporting organization. Using Interpretive Phenomenological Analysis data were thematically analyzed against three predetermined themes, attributes they possessed, challenges they faced, and coping skills they used in aiding them to succeed in their positions.